Analisis Biaya Logistik Pada Perusahaan Air Minum Di Surakarta Berdasarkan Pendekatan Biaya Total Menggunakan Activity-Based Costing - Roni Zakaria R.; Yuniaristanto -; Karunia Prasetyawan (Performa: Media Ilmiah Teknik Industri, 2006)
Logistics costs related to effectiveness and efficiency of product flow. Logistics costing conducted based on total cost approach as structured approach to determine the total costs of products or services. The bottled water manufacture in Surakarta, total cost determination of company’s products exactless to explain resources absorbtion by product. This research implements activity-based costing (ABC) system to calculate total costs of product exactly and accurately. ABC system orientated that activity supporting product flow from procurement up to product marketing. ABC system allocates the resources to activities. Then, total product cost determined from activities cost traced to product as object costs based on suitable cost drivers.